ADAPTATION OF A METHOD OF THE FUNCTIONAL AND COST ANALYSIS FOR BUSINESS MANAGEMENT AUTOMATION (ON THE EXAMPLE OF THE AVIATION INDUSTRY) - E. Dzhamay; A. Sazonov; D. Petrov (Вестник университета, 2016)
Possibility of application of a method of the functional and cost analysis for a choice of the concept of development of corporate information system of the enterprise of the aviation industry is proved. Method merits and demerits are revealed. The method of the functional and cost analysis is offered as the operational focused alternative to traditional financial approaches.